2017
DOI: 10.3389/fmicb.2017.02015
|View full text |Cite
|
Sign up to set email alerts
|

The Copper Homeostasis Transcription Factor CopR Is Involved in H2O2 Stress in Lactobacillus plantarum CAUH2

Abstract: Transcriptional factors (TFs) play important roles in the responses to oxidative, acid, and other environmental stresses in Gram-positive bacteria, but the regulatory mechanism of TFs involved in oxidative stress remains unknown in lactic acid bacteria. In the present work, homologous overexpression strains with 43 TFs were constructed in the Lactobacillus plantarum CAUH2 parent strain. The strain overexpressing CopR displayed the highest sensitivity and a 110-fold decrease in survival rate under H2O2 challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The expression of two copper resistance genes by the photosymbiont in P. ficiformis is indicative of oxidation stress in the sponge environment. Expression of the gene copB by Lactobacillus plantarum CAUH2 improves oxidative tolerance as the encoded protein exports copper ions (Yang et al, 2017). Another gene highly expressed in photosymbiont-containing sponges, multicopper oxidase, encodes a factor that has been proposed to contribute to copper detoxification by converting Cu(I) to less toxic Cu(II) in the periplasm of Escherichia coli (Osman and Cavet, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of two copper resistance genes by the photosymbiont in P. ficiformis is indicative of oxidation stress in the sponge environment. Expression of the gene copB by Lactobacillus plantarum CAUH2 improves oxidative tolerance as the encoded protein exports copper ions (Yang et al, 2017). Another gene highly expressed in photosymbiont-containing sponges, multicopper oxidase, encodes a factor that has been proposed to contribute to copper detoxification by converting Cu(I) to less toxic Cu(II) in the periplasm of Escherichia coli (Osman and Cavet, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that under oxidative stress, the copper export ATPase (copB) gene of L. plantarum is inactivated. This enhances its sensitivity to the oxidative stress conditions induced by H 2 O 2 and Cu + or Cu 2+ participating in essential redox reactions 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The copB (export ATPase for copper ions) and copR (inductor-transcription factor) genes are also involved in the response to OS triggered by H 2 O 2 in L. plantarum. It is assumed that these proteins are associated with the chelation of copper ions [86]. The chelating activity of lactobacilli and bifidobacteria is strain-specific [87].…”
Section: Chelation Of Pro-oxidative Metal Ionsmentioning
confidence: 99%